Implementing early childhood education rural primary school in the Gweru district of Zimbabwe. a view from the school head - Mangwaya, Ezron; Sylvan, Blignaut; Shervani, Pillay (International Research Journals, 2016)
This qualitative study focuses on early childhood education implementation in a rural primary school in the Gweru district of Zimbabwe. Adopting the case study research design, the article explores, through a semi-structured interview, a school head's perceptions of a rural primary school's state of readiness for the implementation of early childhood education. The study established that the school head was not prepared (inducted) for the introduction and implementation of early childhood education, early childhood education was taught by paraprofessionals and early childhood education was implemented with little or no resources. Consequently, the teaching of early childhood education left a lot to be desired. The study recommends interventions that curriculum policy planners can utilize in order to create conditions that enable rural primary schools to be ready for installing, implementing and institutionalising early childhood education.